ANALISIS BUTIR SOAL ELEMEN EKONOMI BISNIS DAN ADMINISTRASI UMUM MENGGUNAKAN APLIKASI ANATES VERSI 4 - Agsyarofi’a Nuradinafika; Nur Anisa Afriyanti; Luqman Hakim; Vivi Pratiwi (EDUCATIONAL JOURNAL : General and Specific Research, 2025)
This research activity uses the classical method used in this study to determine the quality of business economics and general administration elements which include validity, differentiation, difficulty level, reliability, and effectiveness of checkers. This type of research uses a descriptive quantitative approach method. This research was conducted by distributing tests and getting responses from students in grade XI SMK / MAK in Surabaya, Sidoarjo and Gresik totaling 25 respondents. The data was collected using observation techniques and then analyzed using the application for windows, namely Anates version 4. The results received are the questions of business economics and general administration elements analyzed with aspects of validity having low quality, quite good differentiating power, quite good difficulty level, reliability that is already reliable, and good exception effectiveness.